If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.5x + -3 = 12 Reorder the terms: -3 + 1.5x = 12 Solving -3 + 1.5x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1.5x = 12 + 3 Combine like terms: -3 + 3 = 0 0 + 1.5x = 12 + 3 1.5x = 12 + 3 Combine like terms: 12 + 3 = 15 1.5x = 15 Divide each side by '1.5'. x = 10 Simplifying x = 10
| 11+8x=01 | | 54-3x=x^2 | | -4(x-5)+2=-20x+22 | | 3(3+4)=3*3+4 | | -8(m-5)=25-5m | | (3)(4)(x)=6 | | 8mx(4m+1)=170 | | -6b(5a-2b)-7(-3ab-4b^2)= | | 45q-32=70q-82 | | a+18=23 | | -2x-6=2-4x-(-x-1) | | (G+8)=2X+H | | 11(x-5)=(x+5) | | -21=2x-9 | | 191-v=89 | | -3(r+6)=-58 | | 3x+2=3(4)+2 | | 4y-4=35-6y | | z^4=28+96i | | 2x-18=3x+8 | | 231=165-y | | x=-12+-3y | | 10G+1=2k+(7X+Y) | | 5r+5-r-5= | | -3.8y=-24 | | 3(3+4)=3x+4 | | 9x^2-26x-35=0 | | 10x=x+81 | | 3x-2(x-9)=2+2x | | 4x+2x-2=12 | | 9x-3+2x-5=2(4x-1) | | 4w-1+9w= |